Antioxidant Profile and Antidiabetic Effect of Oryza sativa var. Pulu Mandoti “Local Golden Rice” from Enrekang (Indonesia) In Silico Approach - Masniawati, Andi; Mustopa, Apon Zaenal; Umar, Muhammad Ruslan; Manguntungi, Baso; Irawan, Herman; Salsabila, Annisa Suryasetya; Yanti, Sahri; Vanggy, Leggina Rezzy; Handoko; Syahrir, Nur Hilal A.; Rahmadani, Kharmila (2024)
Diabetes affects 537 million adults globally, with 19.47 million cases in Indonesia. It arises from insufficient or ineffective insulin production, leading to complications like nephropathy. Due to the adverse effects of conventional medications, there is a growing need for safer alternatives. Functional foods and bioactive compounds show promise in managing diabetes. One such alternative is rice. Indonesia boasts a unique rice variety known as Pulu Mandoti, exclusively cultivated in the Enrekang District, Makassar, Indonesia. This delightful red rice variant offers numerous nutritional benefits. Unlike white rice, red rice is abundant in essential nutrients such as calcium, zinc, magnesium, protein, and fiber. The study focused on Pulu Mandoti, exploring its potential for antidiabetic and antioxidant activities using LC-MS analysis. Twelve (12) compounds were identified within the 1.23–14.41-min retention time range, with Compound 11 (2,2'-methylenebis(dibenzo[b,d]thiophene)) showing the strongest antioxidant potential compared to vitamin C. In molecular docking, Compound 11 exhibited the lowest binding affinity for both alpha-amylase and alpha-glucosidase (–10.5 and –8.7 kcal/mol, respectively), whereas acarbose displayed the highest binding affinity. For antioxidant analysis, Compounds 11 and 5 demonstrated the lowest binding affinities for NADPH oxidase and xanthine oxidoreductase, respectively, whereas vitamin C showed the highest. The coefficient values for drug properties similarity ranged from 0.40–0.76 for antidiabetic drugs, with Compound 5 displaying the highest coefficient value (0.76) and from 0.41–0.68 for antioxidants, with the highest value observed for antioxidant peptide A acetate.
Keywords: Diabetics; Antioxidants